2020
DOI: 10.1371/journal.pntd.0008230
|View full text |Cite
|
Sign up to set email alerts
|

Patients infected with Mycobacterium africanum versus Mycobacterium tuberculosis possess distinct intestinal microbiota

Abstract: Background Mycobacterium tuberculosis complex (MTBC), the causative agent of tuberculosis (TB), is composed of eight subspecies. TB in West Africa, in contrast to other geographical regions, is caused by Mycobacterium africanum (MAF) in addition to M. tuberculosis (MTB), with both infections presenting similar symptoms. Nevertheless, MAF is considered to be hypovirulent in comparison with MTB and less likely to progress to active disease. In this study, we asked whether MAF and MTB infected patients possess di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 51 publications
0
20
0
Order By: Relevance
“…Although it is widely accepted that diet is the major contributor in shaping gut microbiota [ 12 , 13 ], the type and duration of medications, especially antibiotics, can significantly affect gut microbiota composition [ 14 ]. Several viral and bacterial infections were also identified as a disturbing factor of microbiota balance [ 15 , 16 , 17 , 18 ]. Moreover, intestinal dysbiosis has also been linked to increased susceptibility to respiratory infections [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it is widely accepted that diet is the major contributor in shaping gut microbiota [ 12 , 13 ], the type and duration of medications, especially antibiotics, can significantly affect gut microbiota composition [ 14 ]. Several viral and bacterial infections were also identified as a disturbing factor of microbiota balance [ 15 , 16 , 17 , 18 ]. Moreover, intestinal dysbiosis has also been linked to increased susceptibility to respiratory infections [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Respiratory viral infections are highly prevalent, yet only a few studies have explored the impact of respiratory infections on the intestinal microbiota [ 18 , 22 , 23 ]. Respiratory viruses such as influenza [ 22 ], respiratory syncytial virus [ 23 ], SARS coronavirus [ 24 ], adenovirus [ 25 ], and bocavirus [ 26 ] have been detected in fecal samples from patients with upper respiratory tract infections.…”
Section: Introductionmentioning
confidence: 99%
“…In the mouse model with first line ATT, the order Clostridiales decreased during treatment while the family Porphyromonadaceae increased at the end of the treatment. In a clinical study, it was found that ATT impact significantly certain bacterial populations, such as decreasing the family Enterobacteriaceae (phylum Proteobacteria) ( Namasivayam et al., 2017 ; Namasivayam et al., 2020 ). A recent study on the effects of intestinal microbiome on INH efficacy using mice model showed changes into the gut microbiome population and the abolishment of innate immune response against MTB during INH therapy by a downregulation in the expression of MHC-II and CD86 which diminished the antigen presentation ability and activation of myeloid DCs in lung.…”
Section: Impact Of Antituberculosis Treatment On the Gut Microbiomementioning
confidence: 99%
“…The treatment with this regimen is not without consequences and the main problem is the emerging of resistant to strains (mainly Multi Drug Resistant Tuberculosis, MDR-TB) in which case, we need to extend the regimen and a longer period treatment is required (9-20 months) ( Hong et al., 2016 ; Sood et al., 2018 ). The impacts of the ATT in the immune system are not profoundly investigated, some studies showed a persistent dysbiosis in the human gut microbiota for a long term after treatment cessation ( Wipperman et al., 2017 ; Hu et al., 2019 ; Namasivayam et al., 2020 ). This community of the gut microorganisms help the human immunity in maintaining health status, through the production of various metabolites that influence the immunity ( Thomas et al., 2017 ; Somboro et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The progression and outcome of an infection is dependent on many factors, which include the resident host-microbiome and the presence of other pathogens, sometimes from the same genus (Figure 1) (Adami and Cervantes, 2015;Namasivayam et al, 2019Namasivayam et al, , 2020. Mixed-species infections refer to the phenomenon where different species belonging to the same genus concurrently infect a single host (Figure 1).…”
Section: Introductionmentioning
confidence: 99%